PERJUANGAN TOKOH NYAI ONTOSOROH DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANDA TOER: TINJAUAN FEMINISME LIBERAL - Safitri, Regina; Hajrah, Hajrah; Asri, Aswati (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
The Struggle of Nyai Ontosoroh in the Novel Bumi Manusia by Pramoedya Ananta Toer (Overview of Liberal Feminism). The purpose of this research is to describe the struggle waged by Nyai Ontosoroh in the novel Bumi Manusia by Pramoedya Ananta Toer, using the theory of liberal feminism. The method used is descriptive qualitative. The results of the research that have been conducted show some of the struggles made by Nyai Ontosoroh in maintaining her existence as a woman who can still appear in public even though she is only a siri wife. The struggles that have been carried out are active in studying and not giving up despite being oppressed by her social status as a concubine. The conclusion in this study is that Nyai Ontosoroh as a female figure is able to reflect the values of liberal feminism in the novel Bumi Manusia.